Begonia tinuyopensis (sect. Petermannia, Begoniaceae), a new species from Zamboanga Del Norte, Philippines - Mazo, Kean Roe F.; Aribal, Lowell G.; Bustamante, Rene Alfred Anton; Ang, Yu Pin (Phytotaxa, 2021)
Begonia tinuyopensis is described and illustrated as a new species from Zamboanga del Norte, Philippines. This new species resembles B. mearnsii by having a decumbent stem, scattered hairs over the entire plant, terminal inflorescence bearing 2 staminate tepals and 5 pistillate tepals. However, Begonia tinuyopensis is distinct by having sparse pilose (vs. matted with long brown hairs) stems, ovate (vs. suborbicular to subreniform) leaves and glabrous (vs. densely pubescent) ovary. We assign B. tinuyopensis as Endangered (EN) following IUCN Red List Criteria.